1957
DOI: 10.1099/00221287-16-3-721
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Antigenic Variation in Vibrio cholerae

Abstract: SUMMARY: The variations in Vibrio cholerae studied included changes from Ogawa to Inaba type, smooth+rough, and motile-+non-motile. With a sloppy-agar technique it was possible to estimate the rate of formation of thcse variants (i.e. probable mutation rate 1 in 1 0 5 and 1 in lo4, respectively). It was possible to show that the action of antiserum in promoting the change from Ogawa to Inaba was selective rather than mutagenic. With the other two variations studied no selective process had to be considered owi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…V. cholerae O1 strains are known to interconvert between the Ogawa and Inaba forms (Colwell et al, 1995;Garg et al, 2000) and the wbeT gene of the highly conserved wbe region is responsible for the serotype conversion (Garg et al, 2000). The frequency of conversion of Ogawa to Inaba is approximately 10 25 (Bhaskaran & Gorrill, 1957), whereas conversion from Inaba to Ogawa is much rarer and may be dependent on the strain (Manning et al, 1994). Isolation of both Ogawa and Inaba serotypes during this outbreak is suggestive of the same phenomenon.…”
Section: Amk Gen Imp Azm Cep Cfx Amp Car Cip Gat Nal Nor Ofl Cot Tet mentioning
confidence: 80%
“…V. cholerae O1 strains are known to interconvert between the Ogawa and Inaba forms (Colwell et al, 1995;Garg et al, 2000) and the wbeT gene of the highly conserved wbe region is responsible for the serotype conversion (Garg et al, 2000). The frequency of conversion of Ogawa to Inaba is approximately 10 25 (Bhaskaran & Gorrill, 1957), whereas conversion from Inaba to Ogawa is much rarer and may be dependent on the strain (Manning et al, 1994). Isolation of both Ogawa and Inaba serotypes during this outbreak is suggestive of the same phenomenon.…”
Section: Amk Gen Imp Azm Cep Cfx Amp Car Cip Gat Nal Nor Ofl Cot Tet mentioning
confidence: 80%
“…The phenomenon of sero-conversion has been reported by many investigators (2,4,14,20,23). Although the mechanism of the serotype conversion had not been well understood, comparison of the rfbT genes derived from various Ogawa and Inaba strains suggested that the serotype conversion might be caused by genetic alterations of the rfbT gene.…”
Section: Discussionmentioning
confidence: 90%
“…These serotypes, however, are not stable. Conversion of serotypes is known to occur during subculture in vitro, passage in vivo, or even during a pandemic (2,14,20,23). The mechanism of this spontaneous serotype conversion has not been well understood yet.…”
mentioning
confidence: 99%
“…Complementary approaches include statistical modelling of cholera dynamics based on this serotype model, along with stronger surveillance programs and more comprehensive re-challenge studies. The extreme sensitivity to the cross-immunity parameter also some of the variability in immunity cycle lengths of the stochastic model (figure 3), and therefore why trends in serotype dominance may seem irregular or not readily apparent (Bhaskaran & Gorrill 1957;ProMed Digest 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for these fluctuations has not been understood, and the identification of regularities of these patterns is absent (Bhaskaran & Gorrill 1957;ProMed Digest 2005). A long-term cholera dataset provided by the International Centre for Diarrheal Disease Research, Bangladesh allows for the quantitative study of the origin of these serotype patterns (figure 1a).…”
Section: Disease Datamentioning
confidence: 99%